Effect of zeolite application on reducing nitrogen (N), phosphorus (P), potassium (K) and magnesium (Mg) leaching from mineral soil / Muhammad Syazwan Mohd Haniff - Mohd Haniff, Muhammad Syazwan (Faculty of Plantation and Agrotechnology, 2016)
Zeolite can enhance the soil fertility by reducing nutrient losses through leaching. The main objective of this study is to determine the optimum amount of zeolite required for reducing leaching losses of soil nutrient. The soil column leaching method was used with mineral soil obtained from the UiTM oil palm smallholding in Jasin, Melaka. The treatment consists of four zeolite application rates, i.e. 0, 0.5, 1.0 and 1.5 gram per column. Result shows that application of zeolite significantly reduces leaching losses of nitrogen (N) at 1.5 g/column and phosphorus (P) at 0.5 g/column. However, the zeolite treatments did not significantly reduce leaching losses of potassium (K) and magnesium (Mg) from the soil columns.